Orobanche australis Moris ex Bertol. the correct name for O. thapsoides Lojac. (Orobanchaceae) - Domina, Gianniantonio; Uhlich, Holger; Barone, Giulio (Phytotaxa, 2022)
The taxonomic relationships between Orobanche australis and O. thapsoides are analyzed through the study of the original material. These species are also compared with other morphologically similar ones occurring in the Mediterranean (O. canescens, O. pubescens, O. palaestina, O. amethystea). The lectotype of O. palaestina is designated. From the comparison of these taxa it is evident that O. australis and O. thapsoides refer to the same taxon, to which the name O. australis must be given by priority. The distribution of this species includes Sardinia, Sicily, Peninsular Italy and Southern France. It grows on pastures from the sea level to about 1000 m of altitude, host of Asteraceae. An identification key between the species considered and a distribution map is provided.